2021
DOI: 10.1108/ijoa-02-2021-2631
|View full text |Cite
|
Sign up to set email alerts
|

Team culture, employee commitment and job performance in public sectors: a multi-level analysis

Abstract: Purpose The purpose of this paper is to examine the mediating role of employee commitment into the relationship of team culture and job performance at multi-level, in the context of Ethiopian public sectors. Design/methodology/approach In the adopted survey design, data were collected from two sources. In the rural development sector of Bale zone in Oromia regional state of Ethiopia, 108 randomly selected employees participated in the survey and also their corresponding 13 team supervisors. By using referent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…In this context, a model around employee commitment was defined, given that the results obtained from the model test indicate the confirmation of the proposed model along with the introduced dimensions, components, and indicators. Also, since the dimensions and components were prepared from theoretical foundations and research background (Jung et al, 2020;Loan, 2020;Mishra & Kasim, 2023;Rabiul et al, 2022;Rahayu et al, 2019;Ramzgooyan & Hasanpour 2013;Ridwan et al, 2020;Salari, 2016;Shahul Hameed et al, 2022;To & Huang, 2022;Wijaya & Silitonga, 2023;Yasin et al, 2023). Given that the model's components were selected from research and theoretical foundations, it can be stated that the model for developing commitment aligns with theoretical foundations and research backgrounds, and factors defined in the model are confirmed by research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, a model around employee commitment was defined, given that the results obtained from the model test indicate the confirmation of the proposed model along with the introduced dimensions, components, and indicators. Also, since the dimensions and components were prepared from theoretical foundations and research background (Jung et al, 2020;Loan, 2020;Mishra & Kasim, 2023;Rabiul et al, 2022;Rahayu et al, 2019;Ramzgooyan & Hasanpour 2013;Ridwan et al, 2020;Salari, 2016;Shahul Hameed et al, 2022;To & Huang, 2022;Wijaya & Silitonga, 2023;Yasin et al, 2023). Given that the model's components were selected from research and theoretical foundations, it can be stated that the model for developing commitment aligns with theoretical foundations and research backgrounds, and factors defined in the model are confirmed by research.…”
Section: Discussionmentioning
confidence: 99%
“…Employee commitment is not a goal or a tool, as used in many organizations. Instead, it's a management and leadership philosophy about how more people can help contribute to continuous improvement and ongoing organizational success (Mishra & Kasim, 2023). The benefits of employee commitment are as follows: it leads to better performance, attracts and retains employees, results in the development of better products and more suitable services, leads to higher profitability, makes the workplace a safer environment, increases customer satisfaction, allows better management of change, influences management.…”
Section: Introductionmentioning
confidence: 99%
“…But the governance reforms were carried out across the country with the cooperation of both federal and regional governments. Mishra and Kasim (2021) reported that the government of Ethiopia gave a new direction to public sector functioning by introducing initiatives like kaizen, balance score card and change army as a part of GTP II. Public sector employees are receiving training on leadership, motivation and many more to enhance their performance.…”
Section: Methodsmentioning
confidence: 99%
“…But the governance reforms were carried out across the country with the cooperation of both federal and regional governments. Mishra and Kasim (2021) reported that the government of Ethiopia gave a new direction to public sector IJPL 19,1…”
Section: Methodsmentioning
confidence: 99%
“…Commitment towards an organization is described as psychological connection between an employee and organization that makes an employee to stay longer, becomes more involved and improves organizational performance [30,69]. It is also associated with positive outcomes such as high job performance, low turnover, high job satisfaction [6], improved motivation and organization citizenship behaviour [70].…”
Section: Organizational Commitmentmentioning
confidence: 99%